x^2 - 6x + 8 = 0
(x - 4)(x - 2) = 0
x = 2, 4
2007-06-10 10:56:07
·
answer #1
·
answered by Mathematica 7
·
1⤊
2⤋
First: set the equation to "0" - add 8 with both sides (when you move a term to the opposite side, always use the opposite sign).
x^2-6x+8 = -8+8
x^2-6x+8 = 0
SEc: factor - multiply the 1st & 3rd term to get 8. find two numbers that give you 8 when multiplied & -6 (2nd term) when added/subtracted. the numbers are (-2 & -4). rewrite the expression with the new middle terms.
x^2 - 2x - 4x + 8 = 0
*Group "like" terms & factor both sets of parenthesis.
(x^2 - 2x) - (4x + 8) = 0
x(x - 2) - 4(x - 2) = 0
(x-2)(x-4) = 0
Third: solve the "x" variables - set both parenthesis to "0"
a. x - 2 = 0
x-2+2 = 0+2
x = 0+2
x = 2
b. x - 4 = 0
x-4+4 = 0+4
x = 0+4
x = 4
Solutions: 2, 4
2007-06-10 18:15:10
·
answer #2
·
answered by ♪♥Annie♥♪ 6
·
1⤊
0⤋
First, put the equation in standard form:
x^2-6x+8=0
Next, find factors of 8 that add up to 6. Try -4 and -2
(x-4)(x-2) FOIL to check answer, it's correct.
Now set each factor equal to 0 and solve for x
x-4=0
x-2=0
The answers are 4 and 2.
2007-06-10 17:57:21
·
answer #3
·
answered by edgehead_11071981 2
·
0⤊
1⤋
x^2-6x= -8?
+8 +8 Add 8 to both sides
x^2-6x+8 New Equation
(x-4) (x-2) Separate the x's and make sure the two of the numbers are multiplied to become 8, and added to become -6.
And (x-4) (x-2) is your answer =)
2007-06-10 17:58:14
·
answer #4
·
answered by Irrelavant 3
·
1⤊
1⤋
x^2-6x+8=0
(x-4)(x-2)=0
x=4, 2
checking the math
4^2-6(4)=-8
16-24=-8
and
2^2-6(2)=-8
4-12=-8
2007-06-10 17:59:24
·
answer #5
·
answered by gordonmorrison 6
·
0⤊
0⤋
add 8 for both sides
x^2 - 6x + 8 = 0
find two numbers that multiply to 8 and add to -6
the two numbers are -4 and -2
since the leading coefficient is 1, plug the two numbers in factor form
(x - 4) (x -2) = 0
x = 2 or 4
2007-06-10 17:56:40
·
answer #6
·
answered by 7
·
1⤊
1⤋
First write it in standard form
x^2-6x+8
Then find two numbers. _*_=8 AND the same two numbers add to -6
Those numbers are -4 and -2 because if you multiply them they equal -8 and if you add them they equal -6
so now you break it down to
(x -4) (x-2)
x-4 = 0 x-2 = 0
~x= 4 and x= 2~
2007-06-10 21:00:53
·
answer #7
·
answered by k e 3
·
0⤊
0⤋
move all values to the same side:
x^2-6x+8=0
(x-4)(x-2)=0
X = 4 or 2
2007-06-10 17:56:58
·
answer #8
·
answered by Anonymous
·
0⤊
1⤋
x² - 6x + 8 = 0
(x - 4).(x - 2) = 0
x = 2 , x = 4
2007-06-10 17:56:34
·
answer #9
·
answered by Como 7
·
1⤊
1⤋
step 1: move the 8 over to the side with your x's
x2 - 6x + 8 = 0
step 2: factor
(x-4)(x-2)
there's your answer.
2007-06-10 17:56:51
·
answer #10
·
answered by Mister Scott 1
·
0⤊
2⤋